Analysis and Design of Photobioreactors for Microalgae Production I: Method and Parameters for Radiation Field Simulation - Heinrich, Josué Miguel (2012)
Having capabilities for the simulation of the radiation field in suspensions of microalgae constitutes a great asset for the analysis, optimization and scaling-up of photobioreactors. In this study, a combined experimental and computational procedure is presented, specifically devised for the assessment of the oefficients of absorption and scattering, needed for the simulation of such fields. The experimental procedure consists in measuring the radiant energy transmitted through samples of suspensions of microalgae of different biomass concentrations, as well as the forward and backward scattered light. At a microscopic level,suspensions of microalgae are complex heterogeneous media and due to this complexity, in this study they are modeled as a pseudocontinuum, with centers of absorption and scattering randomly distributed throughout its volume. This model was tested on suspensions of two algal species of dissimilar cell shapes: Chlorella sp. and Scenedesmus quadricauda. The Monte Carlo simulation algorithm developed in this study, when used as a supporting subroutine of a main optimization program based on a genetic algorithm, permits the assessment of the physical parameters of the radiation field model. The Monte Carlo algorithm simulates the experiments, reproducing the events that photons can undergo while they propagate through culture samples or at its physical boundaries.